2014
DOI: 10.1371/journal.pone.0100272
|View full text |Cite
|
Sign up to set email alerts
|

Warm Water Bath Stimulates Phase-Shifts of the Peripheral Circadian Clocks in PER2::LUCIFERASE Mouse

Abstract: Circadian clocks in the peripheral tissues of mice are known to be entrained by pulse stimuli such as restricted feeding, novel wheel running, and several other agents. However, there are no reports on high temperature pulse-mediated entrainment on the phase-shift of peripheral clocks in vivo. Here we show that temperature treatment of mice for two days at 41°C, instead of 37°C, for 1–2 h during the inactive period, using a temperature controlled water bath stimulated phase-advance of peripheral clocks in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This suggests that treadmill exercise involves stress factors. Previously, we demonstrated that a core body temperature of 40–41 °C is necessary to cause a phase shift 45 . When mice were treated with exercise, their core body temperature temporarily increased to 38.5–39.0 °C ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that treadmill exercise involves stress factors. Previously, we demonstrated that a core body temperature of 40–41 °C is necessary to cause a phase shift 45 . When mice were treated with exercise, their core body temperature temporarily increased to 38.5–39.0 °C ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Even in mice that were fed the same diet, different reactions may occur if the microbiota is different in the morning or evening. The abdominal temperature, bowel movement, and endocrine system may influence the microbiota diversity [51][52][53][54], and these factors show circadian rhythm [55][56][57]. Thus, the different microbial reactions that were observed based on the soy protein intake in the morning or evening may be explained by the differences in the fasting time before each diet, microbiota circadian oscillations, and gut functional rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced phase shift of the peripheral circadian clocks might also aid in adapting to several environmental conditions, because increased ROS levels are caused by many conditions such as physiological stress, heat stress, ultraviolet radiation, and xenobiotics [ 7 ]. In our previous experiments, physiological stress and heat stress produced phase changes in the PER2::LUC rhythm of peripheral tissues [ 4 27 ]. In case of restraint stress, we identified phase advance in the peripheral PER2::LUC rhythm after 3 days of 2-h restraint stress during ZT4–6 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of restraint stress, we identified phase advance in the peripheral PER2::LUC rhythm after 3 days of 2-h restraint stress during ZT4–6 [ 4 ]. In case of heat stress, we investigated phase advance in the peripheral PER2::LUC rhythm after warm water bath stimulation during ZT4–6 with temperature dependency [ 27 ]. Restraint stress activates glucocorticoid release as well as the sympathetic nerve system, and the administration of Dex, adrenaline, or noradrenaline caused similar phase shift in the PER2::LUC rhythm of the peripheral tissues through the glucocorticoid- or CREB-responsive elements in the promoter region of several clock genes [ 4 28 29 ].…”
Section: Discussionmentioning
confidence: 99%